Keratinocyte-derived small extracellular vesicles supply antigens for CD1a-resticted T cells and promote their type 2 bias in the context of filaggrin insufficiency - Kobiela, Adrian; Hewelt-Belka, Weronika; Frąckowiak, Joanna E.; Kordulewska, Natalia; Hovhannisyan, Lilit; Bogucka, Aleksandra; Etherington, Rachel; Piróg, Artur; Dapic, Irena; Gabrielsson, Susanne; Brown, Sara J.; Ogg, Graham S.; et al. (Frontiers in Immunology, 2024)
CD1a-restricted T cell responses to lipid antigens are major contributor to allergic inflammation, including in the setting of atopic dermatitis (AD). Here we present the evidence that the membranes of small extracellular vesicles (sEVs), secreted nanosized organelles and important players in the long-distant cellular communication, constitute a source of antigens suitable for CD1a-mediated presentation to T cells. Lipids enclosed within the sEVs secreted on the background of filaggrin reduction, a hallmark of AD (shFLGsEV) contribute to allergic inflammation and induce a switch from type 1 (interferon-γ-based, homeostatic and inflammation resolution-promoting) to type 2 (interleukin-13-based, proallergic) CD1a-mediated T cell responses. Mechanistically, we determined that the lipidome of shFLGsEV is extensively remodelled and less abundant in the long chain (LCFAs) and polyunsaturated fatty acids (PUFAs) and increased content of the bulky headgroup sphingolipids. As a result, the shFLGsEV lipid repertoire shows reduced content of the permissive (stimulatory) CD1a ligands and tilt in favour of the non-permissive (inhibitory) antigens. Finally, we found that this altered sEV lipidome reflects a generalised alteration in cellular lipidome stemming from downregulation of key enzymes implicated in fatty acid elongation and desaturation, i.e., enzymes of the ACSL, ELOVL and FADS family, in filaggrin insufficient cells and the skin of AD patients. Our data indicate that alteration in cellular lipid metabolism impacts CD1a-dependent T cell responses mediated by sEVs an antigen source and affect the course of inflammation, e.g., by perpetuating allergic bias in AD.